Asymmetrical Dependence Between a Neotropical Mistletoe and its Avian Seed Disperser - Guerra, Tadeu J; Pizo, Marco A (Biotropica, 2014)
The degree of interdependence among interacting species has major implications for our understanding of the coevolutionary process and biodiversity maintenance. However, the mutualism strength among fruiting plants and their seed dispersers remains poorly understood in tropical ecosystems. We evaluated simultaneously the effectiveness of the avian seed dispersers of the mistletoe Struthanthus flexicaulis (Loranthaceae) and the contribution of its fruits to their diets in a highland rocky savanna in southeastern Brazil. The mistletoe fruits are small lipid‐rich pseudoberries available throughout the year. Four passerine birds fed on fruits, but Elaenia cristata (Tyrannidae) was the most effective disperser, responsible for more than 96 percent of the dispersed seeds. This bird swallowed fruits whole, expelling and depositing undamaged seeds by regurgitation and bill wiping on perches. From 646 dispersed seeds, 56 percent were deposited on safe sites, thin live twigs of 38 susceptible host species. Elaenia cristata were predominantly frugivorous, feeding on typically ornithocoric fruits of at least 12 species, but also on arthropods. Although fruits represented 75 percent of the feeding bouts along the year, S. flexicaulis fruits represented only 34 percent of the E. cristata diet. Our results highlight the asymmetrical nature of this mutualistic interaction, with the mistletoe life cycle locally linked to one highly effective seed disperser that is more weakly dependent on mistletoes fruits as a food source. We suggest that merging the seed dispersal effectiveness framework with diet assessment of seed dispersers is needed to clarify the asymmetries in mutualistic pairwise interactions involving plants and their animal partners.